2017
DOI: 10.1186/s12907-017-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate Transporter 1 (MCT1) is an independent prognostic biomarker in endometrial cancer

Abstract: BackgroundEndometrial cancer (EC) is a major health concern due to its rising incidence. Whilst early stage disease is generally cured by surgery, advanced EC has a poor prognosis with limited treatment options. Altered energy metabolism is a hallmark of malignancy. Cancer cells drive tumour growth through aerobic glycolysis and must export lactate to maintain intracellular pH. The aim of this study was to evaluate the expression of the lactate/proton monocarboxylate transporters MCT1 and MCT4 and their chaper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Both MCT1 and MCT4 expression were obviously associated with higher HRs, indicating poor prognosis. The relationship was stronger for MCT4 despite the significant heterogeneity between studies (HR=1.70, 95%CI=1.19-2.42, P=0.003, I 2 =71%) while the relationship in two studies 30,37 reporting their HRs for DFS in solid tumours was less apparent (HR=1.48, 95%CI=1.04-2.10, P=0.03, I 2 =0%, Figure 3C and D).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Both MCT1 and MCT4 expression were obviously associated with higher HRs, indicating poor prognosis. The relationship was stronger for MCT4 despite the significant heterogeneity between studies (HR=1.70, 95%CI=1.19-2.42, P=0.003, I 2 =71%) while the relationship in two studies 30,37 reporting their HRs for DFS in solid tumours was less apparent (HR=1.48, 95%CI=1.04-2.10, P=0.03, I 2 =0%, Figure 3C and D).…”
Section: Resultsmentioning
confidence: 92%
“…There was a significant heterogeneity between a total of 9 studies 19,20,27,29,32-34,36,37 that demonstrated LNM with the expression of MCT1 and MCT4 (I 2 =77% and 63%, respectively). Interestingly, there was a significant association between MCT4 expression (high versus low) and LNM (OR=1.87, 95%CI=1.10– 3.17, P=0.02, Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a comparison of healthy and cancerous cell lines suggested that SLC proteins have greater changes in their coexpression networks than protein kinases [28]. Proteins like SLC2A1, SLC39A14, and SLC16A1 may serve as prognostic biomarkers in cancers due to their central role in the development of cancer and responses to treatments [551][552][553]. Thus, it is imperative to continue studying transport proteins in a comprehensive manner, focusing not only on individual transport functions, but also unraveling the complex relationships between different transporters and metabolic states.…”
Section: Discussionmentioning
confidence: 99%
“…Monocarboxylate Transporter 1 (MCT1) is an important protein for lactic acid and pyruvate uptake by cells, while MCT4 is an important protein for cell transport of lactic acid and pyruvate, which play an important role in regulating lactic acid metabolism. It has been reported that MCT1 was an independent prognostic biomarker in endometrial cancer (99). A recent study reported that the use of monocarboxylic acid transporter (MCT) inhibitors can reverse the inhibition of lactic acid on macrophage lysosomes (100).…”
Section: Type 2 Diabetes and Endometrial Cancermentioning
confidence: 99%